Dipeptidyl peptidase 1 inhibitor crystalline polymorphs and their production method and use
Patent Information
- Application Number
- JP2024549145
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-02-22
- Filing Date
- 2023-02-22
- Publication Date
- 2025-02-28
AI Technical Summary
【0037】 本発明は、以下の有益な効果を有する。
Smart Images

Figure 2025505824000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to the pharmaceutical field, specifically to a crystalline polymorph of a dipeptidyl peptidase 1 inhibitor, and its preparation method and use. [Background technology]
[0002] Dipeptidyl peptidase 1 (DPP1), also known as cathepsin C, is a lysosomal papain family cysteine protease involved in intracellular protein degradation. During neutrophil maturation, DPP1 activates neutrophil serine proteases (NSPs) by cleaving N-terminal dipeptides of target proteins, including neutrophil elastase (NE), proteinase 3 (Pr3), and cathepsin G (CatG). DPP1 is associated with many inflammatory diseases, including Wegener's granulomatosis, rheumatoid arthritis, pulmonary inflammation, and viral infections. Studies have shown that inhibiting DPP1 has excellent therapeutic effects on advanced inflammatory lung diseases caused by neutrophils, such as bronchiectasis, chronic obstructive pulmonary disease (COPD), and acute lung injury. Therefore, suppressing the overactivation of NSPs by targeting DPP1 may have potential therapeutic effects on bronchiectasis.
[0003] In patent application PCT / CN2020 / 114500, a DPP1 small molecule inhibitor of the following formula is prepared, which shows very high DPP1 inhibitory activity, has excellent bioavailability and pharmacokinetic characteristics, and has low toxicity and high safety, and is intended to be used for the treatment of lung diseases such as non-cystic fibrosis bronchiectasis, chronic obstructive pulmonary disease (COPD), acute lung injury and cystic fibrosis bronchiectasis. It is an urgent problem to develop a drug crystal form of a compound that is more suitable for drug formation, especially a crystal form with improved stability, hygroscopicity, storage stability and / or efficacy, to obtain good effects in pharmaceuticals. [ka] Summary of the Invention [Means for solving the problem]
[0004] The present invention provides a crystalline polymorph of the compound of formula I, which has high applicability as a pharmaceutical, and has excellent properties such as high purity, good solubility, stable physical and chemical properties, resistance to high temperature, high humidity and strong light exposure, and low hygroscopicity.
[0005] A crystalline polymorph of the compound of formula I, [ka] Here, n is 0 or 1.
[0006] In some embodiments, the crystalline polymorph of the compound of formula I is an anhydrous crystalline form, i.e., n is 0, and said crystalline polymorph is described as crystalline form B and its powder X-ray diffraction pattern employing Cu-Kα radiation has characteristic diffraction peaks at the following 2θ positions: 12.32±0.2°, 14.30±0.2°, 15.43±0.2°, 16.38±0.2°, and 18.56±0.2°.
[0007] Furthermore, in some embodiments, the powder X-ray diffraction pattern of crystalline form B further comprises characteristic diffraction peaks at the following 2θ positions: 17.06±0.2°, 18.21±0.2°, 18.94±0.2°, 19.59±0.2°, 20.79±0.2°, 21.19±0.2°, 22.55±0.2°, 22.97±0.2°, 23.37±0.2°, 24.25±0.2°, and 25.46±0.2°.
[0008] Furthermore, in some embodiments, the powder X-ray diffraction pattern of crystalline form B has characteristic diffraction peaks at the following 2θ positions:
[0009] [Table 1]
[0010] Moreover, in some embodiments, the powder X-ray diffraction pattern of crystalline form B is essentially as shown in FIG.
[0011] Further, in some embodiments, the crystalline form B has a DSC diagram in FIG. 2 and / or a TGA diagram in FIG.
[0012] In some embodiments, the crystalline polymorph of the compound of formula I is a monohydrate crystalline form, i.e., n is 1, and said crystalline polymorph is described as crystalline form C and its powder X-ray diffraction pattern employing Cu-Kα radiation has characteristic diffraction peaks at the following 2θ positions: 8.93±0.2°, 12.10±0.2°, 14.14±0.2°, 20.38±0.2°, 23.86±0.2°, and 25.07±0.2°.
[0013] Furthermore, in some embodiments, the powder X-ray diffraction pattern of crystalline form C further has characteristic diffraction peaks at the following 2θ positions: 15.19±0.2°, 15.92±0.2°, 16.06±0.2°, 17.55±0.2°, 17.90±0.2°, 18.90±0.2°, 19.10±0.2°, 20.81±0.2°, and 24.33±0.2°.
[0014] Furthermore, in some embodiments, the powder X-ray diffraction pattern of crystalline form C has characteristic diffraction peaks at the following 2θ positions:
[0015] [Table 2]
[0016] Moreover, in some embodiments, the powder X-ray diffraction pattern of crystalline form C is essentially as shown in FIG.
[0017] Further, in some embodiments, the crystalline form C has a DSC diagram in FIG. 7 and / or a TGA diagram in FIG.
[0018] In some embodiments, the crystalline polymorph of the compound of formula I is an anhydrous crystalline form, i.e., n is 0, and said crystalline polymorph is described as crystalline form D and its powder X-ray diffraction pattern employing Cu-Kα radiation has characteristic diffraction peaks at the following 2θ positions: 8.68±0.2°, 11.74±0.2°, 13.64±0.2°, 17.40±0.2°, 18.23±0.2°, 20.12±0.2°, and 26.21±0.2°.
[0019] Furthermore, in some embodiments, the powder X-ray diffraction pattern of crystalline form D further has characteristic diffraction peaks at the following 2θ positions: 8.99±0.2°, 13.51±0.2°, 27.49±0.2°, 32.19±0.2°, and 32.97±0.2°.
[0020] Furthermore, in some embodiments, the powder X-ray diffraction pattern of crystalline form D has characteristic diffraction peaks at the following 2θ positions:
[0021] [Table 3]
[0022] Moreover, in some embodiments, the powder X-ray diffraction pattern of crystalline form D is essentially as shown in FIG.
[0023] Further, in some embodiments, for crystalline form B, crystalline form C or crystalline form D described herein, the crystal size is smaller than 100 μm, in some embodiments, the crystal size is smaller than 90 μm, in some embodiments, the crystal size is smaller than 80 μm, in some embodiments, the crystal size is smaller than 70 μm, in some embodiments, the crystal size is smaller than 60 μm, in some embodiments, the crystal size is smaller than 50 μm, in some embodiments, the crystal size is smaller than 40 μm, in some embodiments, the crystal size is smaller than 30 μm, and in some embodiments, the crystal size is smaller than 20 μm.
[0024] The present invention further provides a pharmaceutical composition, which contains a therapeutically effective amount of crystalline form B, crystalline form C or crystalline form D, and a pharma- ceutically acceptable carrier and / or excipient.
[0025] The present invention further provides the use of crystalline form B, crystalline form C or crystalline form D, or a pharmaceutical composition containing them, in the manufacture of a medicament for treating a DPP1 mediated disease.
[0026] Further, DPP1 mediated diseases include, but are not limited to, non-cystic fibrosis bronchiectasis, cystic fibrosis bronchiectasis, acute lung injury, airway obstructive disease, bronchiectasis, cystic fibrosis, asthma, emphysema, and chronic obstructive pulmonary disease.
[0027] Crystalline form B, crystal form C or crystal form D according to the present invention is present at about 5% to about 100% by weight of the API, in some embodiments, at about 10% to about 100% by weight of the API, in some embodiments, at about 15% to about 100% by weight of the API, in some embodiments, at about 20% to about 100% by weight of the API, in some embodiments, at about 25% to about 100% by weight of the API, in some embodiments, at about 30% to about 100% by weight of the API, in some embodiments, at about 35% to about 100% by weight of the API, in some embodiments, at about 40% to about 100% by weight of the API, in some embodiments, at about 45% to about 100% by weight of the API, in some embodiments, at about 50% to about 100% by weight of the API, in some embodiments, at about 55% to about 100% by weight of the API, and in some embodiments, at about 60% to about 100% by weight of the API. in which the API is present at about 60% to about 100% by weight, in some embodiments at about 65% to about 100% by weight of the API, in some embodiments at about 70% to about 100% by weight of the API, in some embodiments at about 75% to about 100% by weight of the API, in some embodiments at about 80% to about 100% by weight of the API, in some embodiments at about 85% to about 100% by weight of the API, in some embodiments at about 90% to about 100% by weight of the API, in some embodiments at about 95% to about 100% by weight of the API, in some embodiments at about 98% to about 100% by weight of the API, in some embodiments at about 99% to about 100% by weight of the API, and in some embodiments, essentially all of the API is crystalline form B, crystalline form C, or crystalline form D, i.e., the API is essentially pure crystalline.
[0028] The present invention further provides a method for preparing said crystalline form B, crystalline form C or crystalline form D, said method comprising the steps of: (1) Suspending and stirring the crude free base of the compound of formula I in a solvent, and filtering to obtain a crystalline form; or (2) The method includes adding a crude free base of the compound of formula I to a solvent, dissolving the crude free base by increasing the temperature, crystallizing the crude free base by decreasing the temperature, and filtering the crude free base to obtain a crystalline form.
[0029] In some embodiments, crystalline form B is obtained by suspending the free base of compound I in IPAc solvent and stirring for 2-5 days.
[0030] In some embodiments, crystalline form B can be obtained by dissolving the free base of Compound I in a mixed solvent of a nitrile solvent and an alcohol solvent at elevated temperature, and then crystallizing the resultant solution at reduced temperature.
[0031] In some embodiments, the nitrile solvent is selected from acetonitrile and the alcohol solvent is selected from methanol, ethanol, propanol, isopropanol, or a combination thereof.
[0032] In some embodiments, the solvent is a mixture of acetonitrile and ethanol.
[0033] In some embodiments, the volume ratio of the nitrile solvent to the alcohol solvent is (1-3):(1-3), in some embodiments, the volume ratio of the nitrile solvent to the alcohol solvent is (1-2):(1-2), and in some embodiments, the volume ratio of the nitrile solvent to the alcohol solvent is 1:1.
[0034] In some embodiments, the clear solution is first cooled to 50 to 60°C, and then seed crystals (which may be obtained by other methods, for example, those produced by the method described in the previous embodiment) are added, followed by further cooling and crystallization.
[0035] In some embodiments, crystalline form C is obtained by suspending the free base of compound I in HO and stirring for 2-5 days.
[0036] In some embodiments, crystalline form D is obtained by dissolving the free base of Compound I in an alcoholic solvent at elevated temperature and then slowly cooling the solution to crystallize it. In some embodiments, the alcoholic solvent is selected from methanol, ethanol, propanol, isopropanol, or a combination thereof. In some embodiments, the solvent is methanol.
[0037] The present invention has the following beneficial effects:
[0038] The crystalline form of the present invention has excellent physicochemical properties, such as good fluidity and significantly improved adhesion, which allows the crystalline form of the present invention to significantly reduce the filtration time during preparation, shorten the production cycle and save costs; the good light stability, heat stability and humidity stability of the crystalline form can ensure the reliability during storage and transportation, thereby ensuring the safety of the preparation and its efficacy after long-term storage; the crystalline form does not need special packaging treatment to prevent the effects of light irradiation, temperature and humidity, thereby reducing costs; the crystalline form will not decompose due to light irradiation, high temperature and high humidity, so patients taking the crystalline form do not need to worry about the photosensitivity reaction of the preparation due to exposure to sunlight; and the crystalline form further has high solubility, which is favorable for the dissolution of the drug and improves bioavailability.
[0039] The crystalline form of the present invention further has good stability, for example, the crystalline form of the present invention does not change after a DVS test ((60% RH-95% RH-0% RH-95% RH or 0% RH-95% RH-0% RH)) or after being left for one week to one month under 25°C / 60% RH and 40°C / 75% RH conditions, and further has polishing stability.
[0040] In addition, the method for preparing the crystalline form of the present invention is simple and efficient, and easy to scale up. The crystalline form has good flowability, good compressibility, high bulk density, low hygroscopicity, and uniform particle size distribution, making it convenient for use in the production of pharmaceutical preparations.
[0041] The preparations prepared using the crystalline form of the present invention can reduce irritation and improve absorption, solve the problem of metabolic rate, significantly reduce toxicity, improve safety, and effectively ensure the quality and efficacy of the preparations.
[0042] As can be appreciated, thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC) are well known in the art, and the height of the melting peaks in the TGA and DSC curves depend on many factors related to sample preparation and instrument geometry, and the peak positions are relatively insensitive to experimental details. Therefore, in some embodiments, the crystalline compounds of the present invention are required to have TGA and DSC patterns with characteristic peak positions and have substantially the same properties as the TGA and DSC patterns according to the drawings of the present invention, with a measurement error tolerance within ±5°C, and typically within ±3°C.
[0043] As will be understood, the numerical values described and protected by this invention are approximations, and variations in the numerical values can be due to instrument calibration, instrument error, crystal purity, crystal size, sample size, and other factors.
[0044] As can be understood, the crystalline forms of the present invention are not limited to those with characteristic spectra, e.g., XRPD, DSC, TGA, DVS, isothermal adsorption curve diagrams, that are exactly the same as those depicted in the figures disclosed in the present invention, and any crystalline form having characteristic spectra that are basically the same or essentially the same as those depicted in the figures is within the scope of the present invention.
[0045] A "therapeutically effective amount" is an amount of a compound that elicits a physiological or medical response in a tissue, system, or subject, which is desired, and includes an amount of the compound that is sufficient, when administered to a subject, to prevent the occurrence of, or alleviate to some extent, one or more symptoms of the disease or condition being treated.
[0046] "Room temperature": 10℃~30℃.
[0047] The term "carrier" refers to a system that does not significantly stimulate the living body, does not eliminate the biological activity and properties of a given compound, and can change the administration form and distribution of a drug in the human body, control the release rate of the drug, and deliver the drug to a target organ. Non-limiting examples include microcapsules and microspheres, nanoparticles, liposomes, etc.
[0048] "Excipient" refers to a substance that is not a therapeutic agent itself, but is added to a pharmaceutical composition as a diluent, adjuvant, adhesive and / or vehicle to improve its processing or storage properties, or to permit or facilitate the compound or pharmaceutical composition to form a dosage form for administration. As known to those skilled in the art, pharmaceutical excipients can serve a variety of functions and may be described as wetting agents, buffers, suspending aids, lubricants, emulsifiers, disintegrants, absorbents, preservatives, surfactants, colorants, flavoring agents and sweeteners. Examples of pharmaceutical excipients include, but are not limited to, the following: (1) sugars, such as lactose, glucose, and sucrose; (2) starches, such as corn starch and potato starch; (3) cellulose and its derivatives, such as sodium carboxymethylcellulose, ethylcellulose, cellulose acetate, hydroxypropyl methylcellulose, hydroxypropyl cellulose, microcrystalline cellulose, and crosslinked carboxymethylcellulose (e.g., crosslinked sodium carboxymethylcellulose); (4) tragacanth gum powder; (5) malt; (6) gelatin; (7) talc; (8) excipients. excipients, such as cocoa butter, suppository waxes, (9) oils, such as peanut oil, cottonseed oil, safflower oil, goa oil, olive oil, corn oil, and soybean oil, (10) glycols, such as propylene glycol, (11) polyols, such as glycerin, sorbitol, mannitol, and polyethylene glycol, (12) esters, such as ethyl oleate and ethyl laurate, (13) agar, (14) buffers, such as magnesium hydroxide and aluminum hydroxide, (15) alginic acid, (16) water for endotoxin testing, (17) isotonic saline, (18) Ringer's solution, (19) ethanol, (20) pH buffer solutions, (21) polyesters, polycarbonates, and / or polyanhydrides, and (22) other non-toxic, compatible substances used in drug formulations.
[0049] "Crystal form" or "crystal" or "crystalline polymorph" refers to any solid material that exhibits three-dimensional arrangement and, in contrast to an amorphous solid material, produces a characteristic XRPD pattern with well-defined peaks.
[0050] The term "seed crystal" refers to the addition of an insoluble additive in a crystallization method to form a crystal nucleus and accelerate or promote the growth of crystals of the same enantiomer with the same crystal shape or configuration.
[0051] "X-ray powder diffraction pattern (XRPD pattern)" refers to an experimentally observed diffraction pattern or parameters, data, or values derived therefrom. XRPD patterns are typically characterized by peak positions (abscissa) and / or peak intensities (ordinate).
[0052] "2θ" refers to the peak position, expressed in degrees (°), set up in an X-ray diffraction experiment, and is typically the abscissa unit in a diffraction pattern. If a reflection is diffracted when the incident beam makes a θ angle with a lattice plane, then the experimental set up requires recording the reflected beam at 2θ angles. It should be understood that the specific 2θ values of a particular crystalline form referred to herein are intended to represent 2θ values (expressed in degrees) measured using the X-ray diffraction experimental conditions described herein.
[0053] The terms "essentially the same" or "essentially as shown in Figure XX" for X-ray diffraction peaks are meant to take into account the typical peak position and intensity variations. For example, as one of ordinary skill in the art would understand, the peak positions (2θ) will show some variation, typically up to 0.1-0.2°, and the instrument used to measure the diffraction will also produce some variation. Also, as one of ordinary skill in the art would understand, the relative peak intensities will vary depending on the instrumental differences and the degree of crystallinity, preferred orientation, sample surface prepared, and other factors known to one of ordinary skill in the art, and should be considered merely a qualitative measurement. [Brief description of the drawings]
[0054] [Figure 1] 1 is a powder X-ray diffraction pattern of crystalline form B. [Diagram 2] 1 is a differential scanning calorimetry analysis curve pattern of crystalline form B. [Diagram 3] 1 is a thermogravimetric analysis pattern of crystalline form B. [Figure 4] This is the nuclear magnetic pattern of crystalline form B. [Diagram 5] 1 is a variable temperature XRPD test pattern of crystalline form B. [Figure 6] 1 is a powder X-ray diffraction pattern of crystalline form C. [Figure 7] 1 is a differential scanning calorimetry analysis curve pattern of crystalline form C. [Figure 8] 1 is a thermogravimetric analysis pattern of crystalline form C. [Figure 9] 1 is a powder X-ray diffraction pattern of crystalline form D. [Figure 10] FIG. 1 is a PLM diagram of crystalline form B. [Figure 11] FIG. 1 is a PLM diagram of crystalline form C. [Figure 12] FIG. 2 is a DVS diagram of crystalline form B. [Figure 13] FIG. 2 is a DVS diagram of crystalline form C. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0055] The present invention will be described in detail below with reference to examples. Unless specific conditions are specified in the examples, the experiments were carried out according to general conditions. The examples given are for better illustrating the present invention, and it should be understood that the present invention is not limited to the examples given. Non-essential improvements and adjustments made to the embodiments by those skilled in the art based on the above invention still fall within the scope of protection of the present invention.
[0056] [Table 4]
[0057] The XRPD measurements were performed using a Panalytical EMPYREAN X-ray powder diffractometer. The scanning parameters are shown in Table 2.
[0058] [Table 5]
[0059] TGA and DSC measurements were taken on a TA Q5000 / 5500 thermogravimetric analyzer and a TA 2500 differential scanning calorimeter, respectively, with the test parameters as shown in Table 3.
[0060] [Table 6]
[0061] The known starting materials of the present invention may be synthesized using or according to methods known in the art, or may be purchased from companies such as Taitan Technology, Ananji Chemical, Shanghai Demo, Chengdu Kelong Chemical, Shaoyuan Chemical Technology, and Bailingwei Technology.
[0062] Unless otherwise stated in the examples, the solutions are aqueous solutions.
[0063] Example 1 Preparation of Compound I (S)-N-((S)-1-cyano-2-(2-fluoro-4-(3-methyl-2-oxo-2,3-dihydrobenzo[d]oxazol-5-yl)phenyl)ethyl)-1,4-oxazepane-2-carboxamide (Compound I) Step 1: [ka]
[0064] Reaction: In a 50L reaction vessel, 10.005 kg of 1,4-dioxane, 1.600 kg of compound a-1 (see the method of patent WO 2015110826A1) and 2.000 kg of compound a-2 (see the method of patent WO 2016139355A1) were added while stirring, and 6.605 kg of potassium carbonate aqueous solution (1.600 kg of potassium carbonate was dissolved in 5.005 kg of purified water) was added. After completion, the atmosphere was replaced with nitrogen gas three times. 100.0 g of [1,1'-bis(diphenylphosphine)ferrocene]dichloride palladium dichloromethane complex was added, and the atmosphere was replaced with nitrogen gas once. Under the protection of nitrogen gas, the reaction solution was heated to 80±5°C and reacted for about 2 hours, after which it was sampled and monitored by HPLC. The center control target value of the content of compound a-2 was ≦1.0%, and the reaction was stopped.
[0065] Post-treatment: add 5.000kg purified water to the reaction liquid, cool to 10±5℃, add 10.005kg purified water, stir and crystallize at 10±5℃ for about 1 hour, filter, wash the filter cake twice with 2.500kg purified water / time, and collect the filter cake.Add 12.605kg absolute ethanol and the filter cake to a 50L reactor, stir at 20±5℃ for about 0.5 hours, filter, wash the filter cake twice with 1.000kg absolute ethanol / time, and collect the filter cake.
[0066] Drying: The filter cake was dried at 55±5° C. under vacuum≦−0.07 MPa for about 16 hours to obtain 2.143 kg of compound a, with a molar yield of 89.4%.
[0067] 1 H NMR (400MHz,DMSO) δ 7.90 (s,1H),7.72-7.30 (m,6H),4.72 (s,1H),3.41 (d,3H),3.09-3.21(m,2H),1.37 (s,9H).
[0068] LCMS m / z = 356.1 [M-56+H] + . Step 2: [ka]
[0069] Reaction: In a 50L glass reactor, add 16.785kg acetonitrile, 2.1381kg compound a and 2.950kg p-toluenesulfonic acid monohydrate while stirring. After completion, control the temperature at 25±5℃, react for about 2 hours, then sample and monitor by HPLC, center control target value compound a content is ≦1.0%, and stop the reaction.
[0070] Post-treatment: Filtration, washing the filter cake with 1.670 kg of acetonitrile, and collecting the filter cake. 2.1381 kg of acetonitrile and the filter cake were added to the reactor, heated to 80±5°C, and stirred for 3 hours. The temperature was further lowered to 20±5°C, and stirred for 1 hour. Filtration, washing the filter cake with 1.670 kg of acetonitrile, and collecting the filter cake.
[0071] Drying: The filter cake was dried at 55±5° C. under vacuum≦−0.07 MPa for about 16 hours. 2.141 kg of compound b was obtained, and the yield was 85.5%.
[0072] 1 H NMR (400MHz,DMSO) δ 9.04 (s,3H),7.70-7.37 (m,8H),7.13 (d,2H),4.90 (dd,1H),3.41 (s,3H),3.29 (t,2H),2.29 (s,3H).
[0073] LCMS m / z =312.2 [M-172+H] + . Step 3: [ka]
[0074] Reaction: In a 100L reactor, add 19.060kg ethyl acetate, 2.1413kg compound b and 1.1300kg compound b-1 (purchased from Nanjing Yaoshi Technology Co., Ltd.) while stirring, and then add 1.725kg N,N-diisopropylethylamine. After completion, under the protection of nitrogen gas, the reaction solution is cooled to 5±5℃, the temperature is controlled at 10±5℃, and 4.240kg propylphosphonic anhydride is added dropwise. After completion, keep warm at 25±5℃ and react for about 3 to 8 hours.
[0075] Post-treatment: The reaction solution was washed in order with sodium bicarbonate solution (1.070 kg of sodium bicarbonate was dissolved in 20.350 kg of water), citric acid solution (2.150 kg of citric acid monohydrate was dissolved in 19.275 kg of water), and sodium chloride (4.300 kg of sodium chloride was dissolved in 17.135 kg of water). 0.210 kg of medicinal charcoal was added to the organic phase and stirred for about 0.5 hours. 0.540 kg of diatomaceous earth was placed on the ground and filtered, and the filter cake was washed with 1.905 kg of ethyl acetate. 1.070 kg of anhydrous sodium sulfate was added to the organic phase and dried for about 0.5 hours. Filtration was performed, and the filter cake was washed with 1.905 kg of ethyl acetate, and the filtrates were combined.
[0076] Concentration: The filtrate was concentrated under reduced pressure at 50±5° C. until no clear fractions were obtained, giving 2.385 kg of compound c (overweight, calculated at 100% yield), which was used directly in the next step reaction.
[0077] 1 H NMR (400MHz,CDCl3) δ 7.54-7.01 (m,7H),5.18 (s,1H),4.25-3.94 (m,3H),3.54 (dd,2H),3.46 (s,3H),3.39-3.04 (m,4H),1.99 (d,2H),1.54-1.39 (m,9H).
[0078] LCMS m / z =483.2 [M-56+1] + . Step 4: [ka]
[0079] Reaction: In a 50L double-glazed reaction vessel containing the concentrate of compound c, 9.305 kg of acetonitrile and 2.530 kg of p-toluenesulfonic acid monohydrate were added while stirring. After completion, the mixture was kept at 25±5°C and reacted for about 2 hours, after which it was sampled and monitored by HPLC. The content of compound c in the center control target value was ≦1.0%, and the reaction was stopped.
[0080] Post-treatment: The reaction solution was cooled to 10±5°C, and diluted ammonia water (1.075 kg of ammonia water and 36.000 kg of purified water were mixed) was added dropwise, and the temperature was controlled to 25°C or less during the dropwise addition. After completion, the temperature was further lowered to 10±5°C, and crystallization was carried out for 2 hours. Filtered, and the filter cake was washed with 11.930 kg of purified water. The filter cake and 14.890 kg of ethanol were added to a 50L double-glazed reaction kettle, stirred at 20±5°C for 0.5 hours, filtered, and the filter cake was washed with 1.860 kg of ethanol, and the filter cake was collected. The filter cake was dried at 55±5°C and a vacuum degree≦-0.07MPa for about 13 hours to obtain 1.6627 kg of crude compound I, with a molar yield of 85.6%.
[0081] Purification: In a 100L reactor, 9.100kg of acetonitrile, 9.220kg of anhydrous ethanol and 1.6627kg of compound (1) crude were added under stirring, heated to an internal temperature of 75±5°C, stirred until dissolved, and filtered while hot. The filtrate was transferred to a 100L reactor (if the product precipitates in the filtrate, it needs to be heated to dissolve), cooled to 35±5°C under stirring, kept warm until obvious solid precipitates, and further stirred while kept warm for about 0.5 hours. The temperature was further cooled to 5±5°C, and kept warm for 2 hours to crystallize. Filtered, the filter cake was washed with 1.300kg of ethanol, and the filter cake was collected.
[0082] Drying: The filter cake was dried at 55±5° C. and vacuum≦−0.07 MPa for about 25 hours to obtain 1.4060 kg of the compound of formula 1 free base, with a yield of 84.6%.
[0083] 1 H NMR (400MHz,DMSO) δ 8.69 (d,1H),7.64 (d,1H),7.61-7.51 (m,2H),7.46 (t,2H),7.39 (d,1H),5.06 (q,1H),4.01 (dd,1H),3.87 (ddd,1H),3.73 (ddd,1H),3.40 (s,3H),3.34-3.28 (m,1H),3.20 (dd,1H),3.06 (dd,1H),2.78 (ddd,1H),2.69-2.54 (m,2H),2.21 (s,1H),1.84-1.63 (m,2H).
[0084] LCMS m / z =439.2 [M+1] + .
[0085] Example 2 Preparation of Crystalline Form B of Compound I 200 mg of the compound prepared in Example 1 was weighed out, suspended in IPAc solvent at room temperature, stirred for 3 days, filtered and dried. XRPD test was performed on the sample, and the free base crystalline form was described as crystalline form B.
[0086] Its XRPD pattern is shown in FIG. 1, and the peak positions of the XRPD diffraction peaks are shown in Table 4.
[0087] [Table 7]
[0088] The DSC / TGA results are shown in Figures 2 and 3, which indicate that the sample has a weight loss of 2.3% when it is heated to 150°C, and has one endothermic peak at 181.9°C (onset temperature). Nuclear magnetic results (Figure 4) indicate that the molar ratio of the residual solvent IPAc to API in the sample is 0.01 (corresponding to a weight loss of 0.1 wt%). For the TGA weight loss study of crystalline form B, variable temperature XRPD test was performed on it (Figure 5) which shows that when free base crystalline form B is purged with nitrogen gas for 20 minutes, heated to 120°C, and cooled down to 30°C, none of the crystalline forms change (some of the diffraction peaks at 120°C are shifted, which is presumed to be due to lattice expansion at high temperature), so it is presumed that free base crystalline form B is an anhydrous crystalline form.
[0089] Example 3 Preparation of Crystalline Form B of Compound I Weighed out 1.0 g of the compound prepared in Example 1, added 5 ml of acetonitrile and 5 ml of ethanol. Heat until dissolved, slowly cool to 50-60°C, add seed crystals (Example 2), continue to cool to room temperature, filter, and dry. The sample was characterized by XRPD, DSC, and TGA, and was crystalline form B.
[0090] Example 4 Preparation of Crystalline Form B of Compound I 4.0 g of the compound prepared in Example 1 was weighed out, 15 ml of dimethyl sulfoxide was added, and the mixture was heated to 75° C. to dissolve it. After dissolution, 70 ml of ethanol was added, and the mixture was stirred and kept warm for 30 minutes. The seed crystals obtained in Example 3 were added, the mixture was cooled to room temperature, filtered, and dried to obtain 3.36 g of crystalline form B, with a yield of 84.0%.
[0091] Example 5 Preparation of Monohydrate Crystal Form C of Compound I 200mg of the compound prepared in Example 1 was weighed out, suspended in H2O at room temperature, stirred for 3 days, filtered and dried. XRPD test was performed on the sample, and the crystal form was described as crystal form C.
[0092] The XRPD pattern is shown in FIG. 6, and the peak positions of the XRPD diffraction peaks are shown in Table 5.
[0093] [Table 8]
[0094] The DSC / TGA results are shown in Figures 7 and 8, and the results show that the sample has a weight loss of 4.5% when heated to 150°C, and has three endothermic peaks at 103.5, 113.4 and 183.0°C (peak temperatures). After heating it to 120°C and cooling to room temperature, the XRPD test showed that the crystal form C transformed into the crystal form B after heating. Due to the crystal transformation after the sample was heated, coupled with the gradual weight loss of the TGA, it was inferred that the crystal form C was a monohydrate.
[0095] Example 6 Preparation of Crystalline Form D of Compound I 200 mg of the compound prepared in Example 1 was weighed out and added to 20 mg of methanol. The mixture was heated to reflux and filtered while hot. The mixture was cooled slowly to room temperature, crystallized, filtered and dried. The crystalline form was described as crystalline form D by XRPD characterization.
[0096] The XRPD pattern is shown in FIG. 9, and the peak positions of the XRPD diffraction peaks are shown in Table 6.
[0097] [Table 9]
[0098] Crystal form evaluation test 1. Crystal form conversion To study the conversion relationship between hydrate crystalline form C and anhydrous crystalline form B, a suspension competition test was conducted. A certain amount of free base was weighed out, and the corresponding solvent was added to suspend at room temperature, stirred for about 2 hours, and then filtered through a 0.45 μm PTFE filter membrane to obtain a saturated solution. 5-7 mg of free base crystalline form B and crystalline form C samples were weighed into HPLC vials, and 1.0 mL of saturated solution was added, suspended and stirred at room temperature, and then solid-state XRPD was tested. The results are summarized in Table 7, and the results show that free base crystalline form B was obtained in the system with water activity of 0-0.2, and crystalline form C was obtained in the system with water activity of 0.4-1.
[0099] [Table 10]
[0100] 2. PLM PLM characterization results for Forms B and C (FIGS. 10-11) showed that the particle size of each sample was smaller than 20 μm.
[0101] 3. Hygroscopicity The hygroscopicity of crystal forms B and C was evaluated by dynamic moisture sorption meter (DVS). Crystal form C was started with ambient humidity (~60%RH), and crystal form B was started with 0% relative humidity (0%RH). In the test, the mass change percentage of the sample was collected with humidity change (60%RH-95%RH-0%RH-95%RH or 0%RH-95%RH-0%RH) under constant temperature condition of 25°C. The test results are shown in Figures 12 and 13, respectively. The results show that crystal forms B and C have moisture adsorption of 0.19% and 0.97% respectively at 25°C / 80%RH, and all samples had no change in crystal form after DVS test. It was shown that the hygroscopicity of the crystal forms of the present invention is low, and the requirements for drug packaging and storage conditions are low.
[0102] 4. Stability of solids Of the compounds used in this experiment, crystalline form B was from Example 3, and crystalline form C was from Example 5. The physical and chemical stability of crystalline forms B and C were tested by XRPD and UPLC, respectively, after they were left uncovered under conditions of 25°C / 60%RH and 40°C / 75%RH. The results are summarized in Table 8. The results show that after each sample was left uncovered under conditions of 25°C / 60%RH and 40°C / 75%RH for one week to one month, the crystalline form did not change and the purity did not decrease obviously, indicating good stability.
[0103] [Table 11]
[0104] 5. Stability Data The compound used in this experiment was from Example 4.
[0105] 5.1 Acceleration test Consideration conditions: 40℃±2℃, 75%RH±5% RH.
[0106] Packaging: The inner packaging material was a double layered low density polyethylene bag, and the outer packaging material was a polyester / aluminum / polyethylene composite bag.
[0107] [Table 12]
[0108] 5.2 Long-term study 1 Consideration conditions: 25℃±2℃, 60%RH±5% RH.
[0109] Packaging: The inner packaging material was a double layered low density polyethylene bag, and the outer packaging material was a polyester / aluminum / polyethylene composite bag.
[0110] [Table 13]
[0111] 5.3 Long-term study 2 Consideration conditions: 30℃±2℃, 65%RH±5%RH.
[0112] Packaging: The inner packaging material was a double layered low density polyethylene bag, and the outer packaging material was a polyester / aluminum / polyethylene composite bag.
[0113] [Table 14]
[0114] 5.4 Long-term study 3 Consideration conditions: 2~8℃.
[0115] Packaging: The inner packaging material was a double layered low density polyethylene bag, and the outer packaging material was a polyester / aluminum / polyethylene composite bag.
[0116] [Table 15] The purity was analyzed by the following method.
[0117] [Table 16]
[0118] Biological Experiments 1. In vitro DPP1 enzyme activity detection experiment Recombinant human DPP1 enzyme (R&D Systems, Cat. No 1071-CY) with a final concentration of 100 μg / mL and recombinant human cathepsin L (R&D Systems, Cat. No 952CY) with a final concentration of 20 μg / mL were mixed and incubated at room temperature for 1 hour to activate the DPP1 enzyme. The activated DPP1 enzyme was diluted 100 times, and 5 μL of compounds with different concentrations and 5 μL of the diluted DPP1 enzyme were added to a 384-well plate and incubated at room temperature for 30 minutes. After adding 10 μL of 20 μM substrate Gly-Arg-AMC (bachem, Cat. No I-1215), the mixture was incubated at room temperature for 60 minutes and the fluorescence intensity was detected by a microplate reader, where the excitation light was 380 nm and the emission light was 460 nm. The IC was measured using the DosResp function in Origin2019 software. 50 values were calculated.
[0119] [Table 17]
[0120] Conclusion: Compound I exhibited highly inhibitory activity against the DPP1 receptor.
[0121] 2. Pharmacokinetic study in rats 1.1 Test animals: male SD rats, approximately 220 g, 6-8 weeks old, 6 rats / compound. Purchased from Chengdu Dashuo Experimental Animal Co., Ltd.
[0122] 1.2 Study design: On the day of the study, six SD rats were randomly divided into groups according to their weight. They were fasted for 12-14 hours without water restriction one day before administration, and fed 4 hours after administration.
[0123] [Table 18]
[0124] Solvent for intravenous administration: 5% DMA + 5% Solutol + 90% Saline, solvent for intragastric administration: 0.5% MC, control compound INS1007 is compound 2 in patent WO 2015110826A1 and was prepared by the method of the patent.
[0125] Before and after administration, 0.1 ml of blood was collected from the orbit under isoflurane anesthesia, placed in an EDTAK2 centrifuge tube, and centrifuged at 5000 rpm, 4°C for 10 min to collect plasma. Blood was collected at 0, 5, 15, 30 min, 1, 2, 4, 6, 8, and 24 h for the intravenous group, and at 0, 5, 15, 30 min, 1, 2, 4, 6, 8, and 24 h for the intragastric group. All samples were stored at -80°C before analysis.
[0126] [Table 19]
[0127] Conclusion: The compounds of the present invention have good bioavailability and pharmacokinetic characteristics.
[0128] 3. Repeated dose toxicity test by oral administration to rats for 14 days SD rats were randomly divided into groups according to body weight, and divided into a solvent control group (0.5% MC), an INS1007 (30, 100, 300 mg / kg) group, and a compound I (30, 100, 300 mg / kg) group. Each treatment group had 16 rats, and the solvent control group had 10 rats. The rats were half male and half female. The corresponding concentration of drug or solvent was administered orally by intragastric administration every day for 14 consecutive days, with a recovery period of 7 days. During the administration period, general symptoms, body weight and food intake were observed for each group, and after the end of the administration period and the end of the recovery period, hematological, serum biochemical and macroscopic anatomical detections were performed for each group.
[0129] Conclusion: At comparable doses, the compounds of the present invention are less toxic and safer than INS1007.
Claims
1. A crystalline polymorph of the compound of formula I, 【Chemistry 1】 A crystalline polymorph of the compound of formula I, wherein n is 0 or 1.
2. 2. The crystalline polymorph according to claim 1, wherein n is 0, the crystalline polymorph is crystalline form B, and the powder X-ray diffraction pattern thereof employs Cu-Kα radiation and has characteristic diffraction peaks at 2θ positions of 12.32±0.2°, 14.30±0.2°, 15.43±0.2°, 16.38±0.2°, and 18.56±0.2°.
3. The crystalline polymorph according to claim 2, wherein the powder X-ray diffraction pattern further has characteristic diffraction peaks at 2θ positions of 17.06±0.2°, 18.21±0.2°, 18.94±0.2°, 19.59±0.2°, 20.79±0.2°, 21.19±0.2°, 22.55±0.2°, 22.97±0.2°, 23.37±0.2°, 24.25±0.2°, and 25.46±0.2°.
4. The crystalline polymorph according to claim 2 or 3, whose powder X-ray diffraction pattern is essentially as shown in FIG.
5. 4. The crystalline polymorph of claim 2 or 3, wherein the crystalline form B has a DSC diagram of FIG. 2 and / or a TGA diagram of FIG.
6. 2. The crystalline polymorph according to claim 1, wherein n is 1, the crystalline polymorph is crystalline form C, and the powder X-ray diffraction pattern thereof employs Cu-Kα radiation and has characteristic diffraction peaks at 2θ positions of 8.93±0.2°, 12.10±0.2°, 14.14±0.2°, 20.38±0.2°, 23.86±0.2°, and 25.07±0.2°.
7. The crystalline polymorph according to claim 6, wherein the powder X-ray diffraction pattern further has characteristic diffraction peaks at 2θ positions of 15.19±0.2°, 15.92±0.2°, 16.06±0.2°, 17.55±0.2°, 17.90±0.2°, 18.90±0.2°, 19.10±0.2°, 20.81±0.2°, and 24.33±0.2°.
8. The crystalline polymorph according to claim 6 or 7, whose powder X-ray diffraction pattern is essentially as shown in FIG.
9. 8. The crystalline polymorph of claim 6 or 7, wherein the crystalline form C has a DSC diagram of FIG. 7 and / or a TGA diagram of FIG.
10. 2. The crystalline polymorph according to claim 1, wherein n is 0, the crystalline polymorph is crystalline form D, and the powder X-ray diffraction pattern thereof employs Cu-Kα radiation and has characteristic diffraction peaks at 2θ positions of 8.68±0.2°, 11.74±0.2°, 13.64±0.2°, 17.40±0.2°, 18.23±0.2°, 20.12±0.2°, and 26.21±0.2°.
11. The crystalline polymorph according to claim 10, wherein the powder X-ray diffraction pattern further has characteristic diffraction peaks at 2θ positions of 8.99±0.2°, 13.51±0.2°, 27.49±0.2°, 32.19±0.2°, and 32.97±0.2°.
12. The crystalline polymorph according to claim 10 or 11, whose powder X-ray diffraction pattern is essentially as shown in FIG.
13. A pharmaceutical composition comprising a therapeutically effective amount of the crystalline polymorph of any one of claims 1 to 3, and a pharma- ceutically acceptable carrier and / or excipient.
14. Use of the crystalline polymorph of any one of claims 1 to 3 in the manufacture of a drug for treating a DPP1 mediated disease.
15. The use according to claim 14, wherein the DPP1 mediated disease is selected from non-cystic fibrosis bronchiectasis, cystic fibrosis bronchiectasis, acute lung injury, airway obstructive disease, bronchiectasis, cystic fibrosis, asthma, emphysema and chronic obstructive pulmonary disease.